Investigating the Accessibility of Education by the Children in Mpigi District as Per the Monitoring Done by the National Childrens Authority - Isaac Mukiza (Uganda Christian University, 2024)
This report investigated the accessibility of education for children in Mpigi district, as monitored by the National Children’s Authority. The study aimed to evaluate the effectiveness of current educational policies, identifying the barriers to accessing education and propose solutions to improve education for all children in the region. By utilization of a mixed methods approach including surveys, interviews and observational data. The research provided a comprehensive overview of the educational landscape in Mpigi district whereby key findings indicated disparities in access based on socioeconomic status, geographical and resource availability. The conclusion encompasses recommendations for policy adjustment, community engagement, and resource allocation to enhance accessibility to resources and necessities to enhance quality, affordable education to all families living in the area. This is to be archived with combined effort from both the families of school going children, the schools, NGO’s, Private sector and the government of Uganda as the lead policy maker